1990
DOI: 10.1002/ajim.4700170307
|View full text |Cite
|
Sign up to set email alerts
|

Parkinson's disease: A case‐control study of occupational and environmental risk factors

Abstract: We compared personal histories of 57 cases and 122 age-matched controls to identify possible environmental determinants of Parkinson's disease (PD). Odds ratios (OR) adjusted for sex, age, and smoking were computed using stepwise logistic regression. We found a statistically significant increased risk for working in orchards (OR = 3.69, p = 0.012, 95% CI = 1.34, 10.27) and a marginally significant increased risk associated with working in planer mills (OR = 4.11, p = 0.065, 95% CI = 0.91, 18.50). A Fisher's ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
154
1
1

Year Published

1993
1993
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 264 publications
(162 citation statements)
references
References 27 publications
6
154
1
1
Order By: Relevance
“…Whilst most studies found similar antibody levels in cases and controls, one study observed higher antibody levels for herpes simplex [538], while another study found lower antibody levels for herpes simplex, rubella and measles [539]. Similarly, studies that examined self-reported history of influenza [132,292,344] or other viral infections [142,411,540] generally reported no association with PD. A case-control study nested within the Harvard Alumni cohort, USA [541] found reduced PD risk associated with measles infection (OR 0.53, 95% CI 0.31-0.93) and another case-control study [411] found increased PD risk associated with diphtheria (OR 2.3, 95% CI 1.2-4.7) and croup (OR 4.1, 95% CI 1.1-16.1).…”
Section: Infectionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Whilst most studies found similar antibody levels in cases and controls, one study observed higher antibody levels for herpes simplex [538], while another study found lower antibody levels for herpes simplex, rubella and measles [539]. Similarly, studies that examined self-reported history of influenza [132,292,344] or other viral infections [142,411,540] generally reported no association with PD. A case-control study nested within the Harvard Alumni cohort, USA [541] found reduced PD risk associated with measles infection (OR 0.53, 95% CI 0.31-0.93) and another case-control study [411] found increased PD risk associated with diphtheria (OR 2.3, 95% CI 1.2-4.7) and croup (OR 4.1, 95% CI 1.1-16.1).…”
Section: Infectionsmentioning
confidence: 99%
“…Of the 34 casecontrol studies that investigated the association between farming and PD, 7 reported an increased risk [290,293,298,303,321,322,344] with ORs that ranged between 1.3 and 5.2.…”
Section: Farming Rural Living Well Water Usementioning
confidence: 99%
“…In particular, Hertzman et al 17 published two reports, in 1990 and 1994. The 1990 study was based on a case-control sample identified in the Kootenay region, a rural mountainous area of British Colombia with a reportedly high PD prevalence.…”
Section: Epidemiological Studiesmentioning
confidence: 99%
“…This led to speculation that paraquat also might be a potential dopamine neurotoxin [22,23]. Several epidemiological studies have reported a positive association between paraquat exposure and the development of PD [24][25][26], although these findings have not been replicated in a large cohort study. Laboratory studies have provided conflicting results.…”
Section: Paraquatmentioning
confidence: 99%